The door of the caliph in the Umayyad al-Andalus : from the conceptualization to the articulation of ceremonial (10th – 11th centuries) - Cardoso, Elsa Raquel Fernandes (2020)
The purpose of this dissertation is to study the conceptualization of the court, palace and ruler of the Umayyad Caliphate of al-Andalus. The Western terminology still plays a normative role in the representation of foreign courts, determining concepts that fit poorly into chronologies and traditions with their own dynamics, hierarchies and specificities, which is the case of the Muslim courts. Far from being the paradigm of court society, the Western court model consists of a case amongst many. Not complying with the Western model and terminology does not mean we are not before a real court society, as in fact the medieval Muslim court model testifies. Such model will be discussed in the light of a courtly common language to the Mediterranean and Eastern societies of the tenth and eleventh centuries. The strong conceptualization of the Umayyad court of Cordoba was further highlighted through the articulation of the ceremonial, as the mis-en-scène of such conceptualization and legitimacy, expressed by gestures, caliphal insignia and hierarchies, which was understood by the Mediterranean and Eastern paradigm of court and ceremonial. Thus, both the conceptualization and the articulation of the ceremonial of Cordoba will be discussed adopting a comparative perspective with the Umayyad Caliphate of Damascus, the ‘Abbasid and Fatimid Caliphates, and the Byzantine Empire. Sources elaborate a specific terminology for the medieval Muslim court societies and, in the specific case of the Umayyad Caliphate of al-Andalus, the court is usually enunciated as Bāb Suddat al-Khalīfa (“The door of the Sudda of the caliph”) – a reference to the symbology associated to the main city gate of Cordoba – or simply as Bāb al-Khalīfa (“the door of the caliph”) and Bāb. Bāb Suddat al-Khalīfa is perhaps the most emblematic concept to name the Umayyad palace and its society, which will be additionally interpreted in the framework of the performance of ceremonial, the language and terminology used in such ceremonies, as well as within the Byzantine and Persian traditions, that overrun the concepts idealized for Western court societies.